Fragment-Based Drug Discovery and X-Ray Crystallography - Davies, Thomas G.; Hyvönen, Marko (Topics in Current Chemistry, 2012)
D. A. Erlanson Introduction to Fragment-Based Drug Discovery T. G. Davies Ian J. Tickle Fragment Screening Using X-Ray Crystallography S. Roughley L. Wright P. Brough A. Massey R. E. Hubbard Hsp90 Inhibitors and Drugs from Fragment and Virtual Screening D. F. Wyss Y.-S. Wang H. L. Eaton C. Strickland J.s H. Voigt Z. Zhu A. W. Stamford Combining NMR and X-ray Crystallography in Fragment-Based Drug Discovery: Discovery of Highly Potent and Selective BACE-1 Inhibitors M. Hennig A. Ruf Walter HuberCombining Biophysical Screening and X-Ray Crystallography for Fragment-Based Drug Discovery E. Valkov T. Sharpe M. Marsh Sa. Greive M. Hyvönen Targeting Protein-Protein Interactions and Fragment-Based Drug Discovery J.h D. Bauman D. Patel E. Arnold Fragment Screening and HIV Therapeutics D. Rognan Fragment-Based Approaches and Computer-Aided Drug Discovery.